Intracytoplazmatická injekce spermie (ICSI) v léčbě nejzávažnějších případů andrologické sterility - Mardešić, Tonko; Zetová, L; Hüttelová, Renata; Müller, P; Vobořil, J; Miková, M; Hulvert, J (Česká gynekologie, 1997)
Intracytoplasmic sperm injection (ICSI) is a procedure which dramatically eliminates the necessity to use donor sperm in androgenically conditioned sterility and enables almost all affected couples to achieve pregnancy.. The results in this group, till recently untreatable, are at least comparable with results achieved in the standard IVF programme. The standard success of the transport IVF programme was confirmed also in the transport IVF-ICSI programme. The transport of gametes does not influence the achieved results. It seems that for the results of the transport programme the indication and possibly other (gynaecological) factors of sterility are decisive. Intracytoplasmic sperm injection has become due to its effectivity an integral part of our IVF programme.
Keywords: Spermatozoa; infertilita; lidé; Female; mužské pohlaví; Male; spermie; ženské pohlaví; Infertility; Humans